TPACK-Based Media Innovation to Enhance Students’ Floral Ornament Drawing Skills - Hasnawati Hasnawati; Aulia Evawani Nurdin; Hotimah Hotimah; Sitti Suryani; Nurainun Muhammad (AL-ISHLAH: Jurnal Pendidikan, 2025)
Floral ornament drawing is a fundamental component of visual arts education, fostering not only technical skills but also creativity and environmental appreciation. However, conventional teaching methods often fail to fully engage students or optimize their creative potential. This study examines the effectiveness of a Technological Pedagogical Content Knowledge (TPACK)-based media innovation in enhancing students’ floral ornament drawing skills. A quasi-experimental design with a post-test-only control group model was employed. The study involved 32 Grade VIII students from SMP Negeri 3 Pattalassang, divided equally into an experimental group using TPACK-based media and a control group using traditional methods. Students were assessed using a standardized drawing rubric evaluating idea originality, creativity of form, color composition, technique, and neatness. Data were analyzed using an independent samples t-test. The experimental group significantly outperformed the control group, achieving a mean score of 91.0 compared to 64.5. The t-test results (t = 8.20, p 0.0001) and a large effect size (Cohen’s d = 2.84) confirmed the substantial impact of the TPACK-based intervention on students’ drawing performance across all criteria. The integration of TPACK-based media effectively enhanced students' technical and creative competencies in floral ornament drawing. This innovation supports more interactive, student-centered, and technology-integrated visual arts instruction, aligned with 21st-century learning goals.